2014
DOI: 10.1210/en.2014-1301
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Origins and Evolutionary Conservation of Intracellular and Neural Signaling Pathways Engaged by the Leptin Receptor

Abstract: In mammals, leptin acts on leptin receptor (LepR) -expressing neurons in the brain to suppress food intake and stimulate whole-body metabolism. A similar action of leptin on food intake has been reported in the frog Xenopus laevis and in several bony fishes. However, the intracellular signaling and neural pathways by which leptin regulates energy balance have not been investigated outside of mammals. Using reporter assays and site-directed mutagenesis we show that the frog LepR signals via signal transducer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 87 publications
(122 reference statements)
3
33
0
Order By: Relevance
“…The present data also agree with studies using peripheral Lep treatment of rainbow trout and Atlantic salmon, indicating that the anorexigenic action of Lep in salmonids is mediated through the Pomc pathway (Murashita et al 2008(Murashita et al , 2011. These data are also in agreement with data on frog Xenopus laevis, where ICV Lep administration increases pomc transcription (Cui et al 2014). Also in mammals, LEP primarily acts on the POMC/CART neurons in the ARC (Varela & Horvath 2012), while in fish, the NLT of the hypothalamus is considered to be homologous to the mammalian ARC (Biran et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present data also agree with studies using peripheral Lep treatment of rainbow trout and Atlantic salmon, indicating that the anorexigenic action of Lep in salmonids is mediated through the Pomc pathway (Murashita et al 2008(Murashita et al , 2011. These data are also in agreement with data on frog Xenopus laevis, where ICV Lep administration increases pomc transcription (Cui et al 2014). Also in mammals, LEP primarily acts on the POMC/CART neurons in the ARC (Varela & Horvath 2012), while in fish, the NLT of the hypothalamus is considered to be homologous to the mammalian ARC (Biran et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…This is further supported by the increased phosphor-Akt-ir cells in this hypothalamic area following a central Lep injection, as the change in intracellular signaling must be induced through the functional Lep receptor. Thus, the LepR L distribution in rainbow trout appears to be similar to that in rat, where the full-length LEPRb is predominantly found within the arcuate, dorsomedial, and ventromedial nuclei (Elmquist et al 1998), as well as in Xenopus, where the LepR is found within the ventral hypothalamus (Cui et al 2014).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Phylogenetic reconstruction revealed that the topologies of vertebrate leptins are consistent with the general understanding of the evolution of vertebrates, corresponding to clades response [64], and to be associated with growth rate [65][66][67][68][69] in different vertebrates. The JAK/STAT pathway is found to be conserved between frogs and mammals [70], suggesting conservation of the leptin signaling mechanism across vertebrate groups. More diverse physiological roles have been characterized in teleosts than those found in mammals [39].…”
Section: Phylogenetic Analysis Of Leptinmentioning
confidence: 99%